The Integration of Spirituality and Ethics in the Construction of Tawhid-Based Ecotheology - Syawaluddin Hanafi; Andi Yaqub; Rahmatun Nair; Abdul Muid Nawawi; Arini Pratiwi; Muspita Sari (International Journal on Advanced Science, Education, and Religion, 2026)
This study aims to reconstruct the paradigm of ecotheology as a response to the global ecological crisis rooted in anthropocentrism and the secularization of the relationship between humans and nature. The research employs a qualitative method using a literature review approach and hermeneutical analysis of Islamic theological sources, particularly the concepts of cosmic tawhid, khalifah (stewardship), mīzān (balance), the prohibition of fasād (corruption/destruction), and ihsan (moral excellence). The findings indicate that an ideal ecotheological paradigm should be developed through the integration of spiritual awareness, ecological ethics, and sustainable social praxis. Ecotheology functions not merely as an environmental ethic, but as an epistemological foundation and civilizational orientation that affirms the interconnectedness of humans, nature, and God. The resulting operational model of ecotheology positions spirituality as the basis of ecological consciousness, ethics as moral regulation, and ecological action as its concrete implementation in social life.